test_recurr.py 11 KB

123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179180181182183184185186187188189190191192193194195196197198199200201202203204205206207208209210211212213214215216217218219220221222223224225226227228229230231232233234235236237238239240241242243244245246247248249250251252253254255256257258259260261262263264265266267268269270271272273274275276277278279280281282283284285286287288289290291292293294295
  1. from sympy.core.function import (Function, Lambda, expand)
  2. from sympy.core.numbers import (I, Rational)
  3. from sympy.core.relational import Eq
  4. from sympy.core.singleton import S
  5. from sympy.core.symbol import (Symbol, symbols)
  6. from sympy.functions.combinatorial.factorials import (rf, binomial, factorial)
  7. from sympy.functions.elementary.complexes import Abs
  8. from sympy.functions.elementary.miscellaneous import sqrt
  9. from sympy.functions.elementary.trigonometric import (cos, sin)
  10. from sympy.polys.polytools import factor
  11. from sympy.solvers.recurr import rsolve, rsolve_hyper, rsolve_poly, rsolve_ratio
  12. from sympy.testing.pytest import raises, slow, XFAIL
  13. from sympy.abc import a, b
  14. y = Function('y')
  15. n, k = symbols('n,k', integer=True)
  16. C0, C1, C2 = symbols('C0,C1,C2')
  17. def test_rsolve_poly():
  18. assert rsolve_poly([-1, -1, 1], 0, n) == 0
  19. assert rsolve_poly([-1, -1, 1], 1, n) == -1
  20. assert rsolve_poly([-1, n + 1], n, n) == 1
  21. assert rsolve_poly([-1, 1], n, n) == C0 + (n**2 - n)/2
  22. assert rsolve_poly([-n - 1, n], 1, n) == C0*n - 1
  23. assert rsolve_poly([-4*n - 2, 1], 4*n + 1, n) == -1
  24. assert rsolve_poly([-1, 1], n**5 + n**3, n) == \
  25. C0 - n**3 / 2 - n**5 / 2 + n**2 / 6 + n**6 / 6 + 2*n**4 / 3
  26. def test_rsolve_ratio():
  27. solution = rsolve_ratio([-2*n**3 + n**2 + 2*n - 1, 2*n**3 + n**2 - 6*n,
  28. -2*n**3 - 11*n**2 - 18*n - 9, 2*n**3 + 13*n**2 + 22*n + 8], 0, n)
  29. assert solution == C0*(2*n - 3)/(n**2 - 1)/2
  30. def test_rsolve_hyper():
  31. assert rsolve_hyper([-1, -1, 1], 0, n) in [
  32. C0*(S.Half - S.Half*sqrt(5))**n + C1*(S.Half + S.Half*sqrt(5))**n,
  33. C1*(S.Half - S.Half*sqrt(5))**n + C0*(S.Half + S.Half*sqrt(5))**n,
  34. ]
  35. assert rsolve_hyper([n**2 - 2, -2*n - 1, 1], 0, n) in [
  36. C0*rf(sqrt(2), n) + C1*rf(-sqrt(2), n),
  37. C1*rf(sqrt(2), n) + C0*rf(-sqrt(2), n),
  38. ]
  39. assert rsolve_hyper([n**2 - k, -2*n - 1, 1], 0, n) in [
  40. C0*rf(sqrt(k), n) + C1*rf(-sqrt(k), n),
  41. C1*rf(sqrt(k), n) + C0*rf(-sqrt(k), n),
  42. ]
  43. assert rsolve_hyper(
  44. [2*n*(n + 1), -n**2 - 3*n + 2, n - 1], 0, n) == C1*factorial(n) + C0*2**n
  45. assert rsolve_hyper(
  46. [n + 2, -(2*n + 3)*(17*n**2 + 51*n + 39), n + 1], 0, n) == 0
  47. assert rsolve_hyper([-n - 1, -1, 1], 0, n) == 0
  48. assert rsolve_hyper([-1, 1], n, n).expand() == C0 + n**2/2 - n/2
  49. assert rsolve_hyper([-1, 1], 1 + n, n).expand() == C0 + n**2/2 + n/2
  50. assert rsolve_hyper([-1, 1], 3*(n + n**2), n).expand() == C0 + n**3 - n
  51. assert rsolve_hyper([-a, 1],0,n).expand() == C0*a**n
  52. assert rsolve_hyper([-a, 0, 1], 0, n).expand() == (-1)**n*C1*a**(n/2) + C0*a**(n/2)
  53. assert rsolve_hyper([1, 1, 1], 0, n).expand() == \
  54. C0*(Rational(-1, 2) - sqrt(3)*I/2)**n + C1*(Rational(-1, 2) + sqrt(3)*I/2)**n
  55. assert rsolve_hyper([1, -2*n/a - 2/a, 1], 0, n) == 0
  56. @XFAIL
  57. def test_rsolve_ratio_missed():
  58. # this arises during computation
  59. # assert rsolve_hyper([-1, 1], 3*(n + n**2), n).expand() == C0 + n**3 - n
  60. assert rsolve_ratio([-n, n + 2], n, n) is not None
  61. def recurrence_term(c, f):
  62. """Compute RHS of recurrence in f(n) with coefficients in c."""
  63. return sum(c[i]*f.subs(n, n + i) for i in range(len(c)))
  64. def test_rsolve_bulk():
  65. """Some bulk-generated tests."""
  66. funcs = [ n, n + 1, n**2, n**3, n**4, n + n**2, 27*n + 52*n**2 - 3*
  67. n**3 + 12*n**4 - 52*n**5 ]
  68. coeffs = [ [-2, 1], [-2, -1, 1], [-1, 1, 1, -1, 1], [-n, 1], [n**2 -
  69. n + 12, 1] ]
  70. for p in funcs:
  71. # compute difference
  72. for c in coeffs:
  73. q = recurrence_term(c, p)
  74. if p.is_polynomial(n):
  75. assert rsolve_poly(c, q, n) == p
  76. # See issue 3956:
  77. if p.is_hypergeometric(n) and len(c) <= 3:
  78. assert rsolve_hyper(c, q, n).subs(zip(symbols('C:3'), [0, 0, 0])).expand() == p
  79. def test_rsolve_0_sol_homogeneous():
  80. # fixed by cherry-pick from
  81. # https://github.com/diofant/diofant/commit/e1d2e52125199eb3df59f12e8944f8a5f24b00a5
  82. assert rsolve_hyper([n**2 - n + 12, 1], n*(n**2 - n + 12) + n + 1, n) == n
  83. def test_rsolve():
  84. f = y(n + 2) - y(n + 1) - y(n)
  85. h = sqrt(5)*(S.Half + S.Half*sqrt(5))**n \
  86. - sqrt(5)*(S.Half - S.Half*sqrt(5))**n
  87. assert rsolve(f, y(n)) in [
  88. C0*(S.Half - S.Half*sqrt(5))**n + C1*(S.Half + S.Half*sqrt(5))**n,
  89. C1*(S.Half - S.Half*sqrt(5))**n + C0*(S.Half + S.Half*sqrt(5))**n,
  90. ]
  91. assert rsolve(f, y(n), [0, 5]) == h
  92. assert rsolve(f, y(n), {0: 0, 1: 5}) == h
  93. assert rsolve(f, y(n), {y(0): 0, y(1): 5}) == h
  94. assert rsolve(y(n) - y(n - 1) - y(n - 2), y(n), [0, 5]) == h
  95. assert rsolve(Eq(y(n), y(n - 1) + y(n - 2)), y(n), [0, 5]) == h
  96. assert f.subs(y, Lambda(k, rsolve(f, y(n)).subs(n, k))).simplify() == 0
  97. f = (n - 1)*y(n + 2) - (n**2 + 3*n - 2)*y(n + 1) + 2*n*(n + 1)*y(n)
  98. g = C1*factorial(n) + C0*2**n
  99. h = -3*factorial(n) + 3*2**n
  100. assert rsolve(f, y(n)) == g
  101. assert rsolve(f, y(n), []) == g
  102. assert rsolve(f, y(n), {}) == g
  103. assert rsolve(f, y(n), [0, 3]) == h
  104. assert rsolve(f, y(n), {0: 0, 1: 3}) == h
  105. assert rsolve(f, y(n), {y(0): 0, y(1): 3}) == h
  106. assert f.subs(y, Lambda(k, rsolve(f, y(n)).subs(n, k))).simplify() == 0
  107. f = y(n) - y(n - 1) - 2
  108. assert rsolve(f, y(n), {y(0): 0}) == 2*n
  109. assert rsolve(f, y(n), {y(0): 1}) == 2*n + 1
  110. assert rsolve(f, y(n), {y(0): 0, y(1): 1}) is None
  111. assert f.subs(y, Lambda(k, rsolve(f, y(n)).subs(n, k))).simplify() == 0
  112. f = 3*y(n - 1) - y(n) - 1
  113. assert rsolve(f, y(n), {y(0): 0}) == -3**n/2 + S.Half
  114. assert rsolve(f, y(n), {y(0): 1}) == 3**n/2 + S.Half
  115. assert rsolve(f, y(n), {y(0): 2}) == 3*3**n/2 + S.Half
  116. assert f.subs(y, Lambda(k, rsolve(f, y(n)).subs(n, k))).simplify() == 0
  117. f = y(n) - 1/n*y(n - 1)
  118. assert rsolve(f, y(n)) == C0/factorial(n)
  119. assert f.subs(y, Lambda(k, rsolve(f, y(n)).subs(n, k))).simplify() == 0
  120. f = y(n) - 1/n*y(n - 1) - 1
  121. assert rsolve(f, y(n)) is None
  122. f = 2*y(n - 1) + (1 - n)*y(n)/n
  123. assert rsolve(f, y(n), {y(1): 1}) == 2**(n - 1)*n
  124. assert rsolve(f, y(n), {y(1): 2}) == 2**(n - 1)*n*2
  125. assert rsolve(f, y(n), {y(1): 3}) == 2**(n - 1)*n*3
  126. assert f.subs(y, Lambda(k, rsolve(f, y(n)).subs(n, k))).simplify() == 0
  127. f = (n - 1)*(n - 2)*y(n + 2) - (n + 1)*(n + 2)*y(n)
  128. assert rsolve(f, y(n), {y(3): 6, y(4): 24}) == n*(n - 1)*(n - 2)
  129. assert rsolve(
  130. f, y(n), {y(3): 6, y(4): -24}) == -n*(n - 1)*(n - 2)*(-1)**(n)
  131. assert f.subs(y, Lambda(k, rsolve(f, y(n)).subs(n, k))).simplify() == 0
  132. assert rsolve(Eq(y(n + 1), a*y(n)), y(n), {y(1): a}).simplify() == a**n
  133. assert rsolve(y(n) - a*y(n-2),y(n), \
  134. {y(1): sqrt(a)*(a + b), y(2): a*(a - b)}).simplify() == \
  135. a**(n/2 + 1) - b*(-sqrt(a))**n
  136. f = (-16*n**2 + 32*n - 12)*y(n - 1) + (4*n**2 - 12*n + 9)*y(n)
  137. yn = rsolve(f, y(n), {y(1): binomial(2*n + 1, 3)})
  138. sol = 2**(2*n)*n*(2*n - 1)**2*(2*n + 1)/12
  139. assert factor(expand(yn, func=True)) == sol
  140. sol = rsolve(y(n) + a*(y(n + 1) + y(n - 1))/2, y(n))
  141. assert str(sol) == 'C0*((-sqrt(1 - a**2) - 1)/a)**n + C1*((sqrt(1 - a**2) - 1)/a)**n'
  142. assert rsolve((k + 1)*y(k), y(k)) is None
  143. assert (rsolve((k + 1)*y(k) + (k + 3)*y(k + 1) + (k + 5)*y(k + 2), y(k))
  144. is None)
  145. assert rsolve(y(n) + y(n + 1) + 2**n + 3**n, y(n)) == (-1)**n*C0 - 2**n/3 - 3**n/4
  146. def test_rsolve_raises():
  147. x = Function('x')
  148. raises(ValueError, lambda: rsolve(y(n) - y(k + 1), y(n)))
  149. raises(ValueError, lambda: rsolve(y(n) - y(n + 1), x(n)))
  150. raises(ValueError, lambda: rsolve(y(n) - x(n + 1), y(n)))
  151. raises(ValueError, lambda: rsolve(y(n) - sqrt(n)*y(n + 1), y(n)))
  152. raises(ValueError, lambda: rsolve(y(n) - y(n + 1), y(n), {x(0): 0}))
  153. raises(ValueError, lambda: rsolve(y(n) + y(n + 1) + 2**n + cos(n), y(n)))
  154. def test_issue_6844():
  155. f = y(n + 2) - y(n + 1) + y(n)/4
  156. assert rsolve(f, y(n)) == 2**(-n + 1)*C1*n + 2**(-n)*C0
  157. assert rsolve(f, y(n), {y(0): 0, y(1): 1}) == 2**(1 - n)*n
  158. def test_issue_18751():
  159. r = Symbol('r', positive=True)
  160. theta = Symbol('theta', real=True)
  161. f = y(n) - 2 * r * cos(theta) * y(n - 1) + r**2 * y(n - 2)
  162. assert rsolve(f, y(n)) == \
  163. C0*(r*(cos(theta) - I*Abs(sin(theta))))**n + C1*(r*(cos(theta) + I*Abs(sin(theta))))**n
  164. def test_constant_naming():
  165. #issue 8697
  166. assert rsolve(y(n+3) - y(n+2) - y(n+1) + y(n), y(n)) == (-1)**n*C1 + C0 + C2*n
  167. assert rsolve(y(n+3)+3*y(n+2)+3*y(n+1)+y(n), y(n)).expand() == (-1)**n*C0 - (-1)**n*C1*n - (-1)**n*C2*n**2
  168. assert rsolve(y(n) - 2*y(n - 3) + 5*y(n - 2) - 4*y(n - 1),y(n),[1,3,8]) == 3*2**n - n - 2
  169. #issue 19630
  170. assert rsolve(y(n+3) - 3*y(n+1) + 2*y(n), y(n), {y(1):0, y(2):8, y(3):-2}) == (-2)**n + 2*n
  171. @slow
  172. def test_issue_15751():
  173. f = y(n) + 21*y(n + 1) - 273*y(n + 2) - 1092*y(n + 3) + 1820*y(n + 4) + 1092*y(n + 5) - 273*y(n + 6) - 21*y(n + 7) + y(n + 8)
  174. assert rsolve(f, y(n)) is not None
  175. def test_issue_17990():
  176. f = -10*y(n) + 4*y(n + 1) + 6*y(n + 2) + 46*y(n + 3)
  177. sol = rsolve(f, y(n))
  178. expected = C0*((86*18**(S(1)/3)/69 + (-12 + (-1 + sqrt(3)*I)*(290412 +
  179. 3036*sqrt(9165))**(S(1)/3))*(1 - sqrt(3)*I)*(24201 + 253*sqrt(9165))**
  180. (S(1)/3)/276)/((1 - sqrt(3)*I)*(24201 + 253*sqrt(9165))**(S(1)/3))
  181. )**n + C1*((86*18**(S(1)/3)/69 + (-12 + (-1 - sqrt(3)*I)*(290412 + 3036
  182. *sqrt(9165))**(S(1)/3))*(1 + sqrt(3)*I)*(24201 + 253*sqrt(9165))**
  183. (S(1)/3)/276)/((1 + sqrt(3)*I)*(24201 + 253*sqrt(9165))**(S(1)/3))
  184. )**n + C2*(-43*18**(S(1)/3)/(69*(24201 + 253*sqrt(9165))**(S(1)/3)) -
  185. S(1)/23 + (290412 + 3036*sqrt(9165))**(S(1)/3)/138)**n
  186. assert sol == expected
  187. e = sol.subs({C0: 1, C1: 1, C2: 1, n: 1}).evalf()
  188. assert abs(e + 0.130434782608696) < 1e-13
  189. def test_issue_8697():
  190. a = Function('a')
  191. eq = a(n + 3) - a(n + 2) - a(n + 1) + a(n)
  192. assert rsolve(eq, a(n)) == (-1)**n*C1 + C0 + C2*n
  193. eq2 = a(n + 3) + 3*a(n + 2) + 3*a(n + 1) + a(n)
  194. assert (rsolve(eq2, a(n)) ==
  195. (-1)**n*C0 + (-1)**(n + 1)*C1*n + (-1)**(n + 1)*C2*n**2)
  196. assert rsolve(a(n) - 2*a(n - 3) + 5*a(n - 2) - 4*a(n - 1),
  197. a(n), {a(0): 1, a(1): 3, a(2): 8}) == 3*2**n - n - 2
  198. # From issue thread (but fixed by https://github.com/diofant/diofant/commit/da9789c6cd7d0c2ceeea19fbf59645987125b289):
  199. assert rsolve(a(n) - 2*a(n - 1) - n, a(n), {a(0): 1}) == 3*2**n - n - 2
  200. def test_diofantissue_294():
  201. f = y(n) - y(n - 1) - 2*y(n - 2) - 2*n
  202. assert rsolve(f, y(n)) == (-1)**n*C0 + 2**n*C1 - n - Rational(5, 2)
  203. # issue sympy/sympy#11261
  204. assert rsolve(f, y(n), {y(0): -1, y(1): 1}) == (-(-1)**n/2 + 2*2**n -
  205. n - Rational(5, 2))
  206. # issue sympy/sympy#7055
  207. assert rsolve(-2*y(n) + y(n + 1) + n - 1, y(n)) == 2**n*C0 + n
  208. def test_issue_15553():
  209. f = Function("f")
  210. assert rsolve(Eq(f(n), 2*f(n - 1) + n), f(n)) == 2**n*C0 - n - 2
  211. assert rsolve(Eq(f(n + 1), 2*f(n) + n**2 + 1), f(n)) == 2**n*C0 - n**2 - 2*n - 4
  212. assert rsolve(Eq(f(n + 1), 2*f(n) + n**2 + 1), f(n), {f(1): 0}) == 7*2**n/2 - n**2 - 2*n - 4
  213. assert rsolve(Eq(f(n), 2*f(n - 1) + 3*n**2), f(n)) == 2**n*C0 - 3*n**2 - 12*n - 18
  214. assert rsolve(Eq(f(n), 2*f(n - 1) + n**2), f(n)) == 2**n*C0 - n**2 - 4*n - 6
  215. assert rsolve(Eq(f(n), 2*f(n - 1) + n), f(n), {f(0): 1}) == 3*2**n - n - 2